Economic Development of Civil Society in Bojonegoro Regency - Purnomo, Joko Hadi; Hidayati, Niswatin Nurul (STAI Auliaurrasyidin Tembilahan, 2024)
Economic problems are universal problems faced by various groups of people. The establishment of a civil society economic order is a shared goal to realize the development of people’s economy, it is an economy that involves the participation of many people, which is the livelihood of many people, which provides benefits to many people, and whose ownership is by many people. This article aimed to describe how the activities in the implemented community assistance program were able to make the community in the area around the forest in Bojonegoro Regency became more empowered, with the process of increasing community capacity and utilizing forest access to improve their economy, as well as how each element of the stakeholders contributed to the process of realizing the economic order of society. The approach used was Participatory Action Research (PAR). The results showed that the assistance program carried out was still running until now and there had been several activities carried out, including starting from coordination with stakeholders, Focus Group Discussions (FGD), community meetings, preparation of SOPs, assessment of business potential and feasibility, providing assistance, mentoring, working meetings, MoU, as well as monitoring and evaluation. The mentoring activities carried out also involved many parties, ranging from the public/government sector, private/business sector, universities, Civil Society Organizations (CSOs), community/beneficiary communities, and mass media.